Depression among men in ART treatment: a register-based national cohort study. Issue 3 (6th June 2020) - Sejbaek, CS; Pinborg, A; Hageman, I; Sørensen, A MS; Koert, E; Forman, JL; Schmidt, L
Abstract: STUDY QUESTION: Are male factor infertility or remaining childless risk factors for unipolar depression among men in assisted reproductive technology (ART) treatment? SUMMARY ANSWER: Male factor infertility was not associated with a significantly increased risk of unipolar depression and men remaining childless did not have a significantly increased risk of developing unipolar depression compared to men in ART treatment who became fathers. WHAT IS KNOWN ALREADY: Men in medically assisted reproduction due to male factor infertility are more distressed and have more negative emotions such as feelings of loss, stigma and low self-esteem compared to men in fertility treatment due to other infertility diagnosis. Stress is in general a risk factor for depression. However, previous studies show conflicting results whether male factor infertility is a risk factor for depression. STUDY DESIGN, SIZE, DURATION: This national, register-based cohort study consisted of 37 913 cohabitant male partners of women in ART treatment recorded in the Danish IVF register (1994–2009). Via a national register, the men's personal identification number data were linked to the Danish Psychiatric Central Research Register (PCRR) (1969–2009) which records psychiatric diagnoses including unipolar depression, based on the ICD-8 and ICD-10 classification system. PARTICIPANTS/MATERIALS, SETTING, METHODS: The full cohort of male partners ( n  = 37 913) was included in the initial analysis on prevalence of unipolar depression before or after ART treatment initiation. The association between male factor infertility and unipolar depression diagnosis after initiating ART treatment was analysed with Cox regression analysis in a sub-study population of men with the exclusion of men having a depression prior to ART treatment or not having full data on educational level and infertility diagnosis ( n  = 34 817). MAIN RESULTS AND THE ROLE OF CHANCE: Overall, 1.2% ( n  = 446) of the men were diagnosed with unipolar depression either before initiating ART treatment ( n  = 146) or during follow-up ( n  = 300). In all, 76.0% of men with depression prior to or after ART treatment achieved fatherhood compared to 82.3% of men without depression ( P  < 0.001). In the sub-study population ( n  = 34 817, which included 266 men with a unipolar depression diagnosis), male factor infertility was not associated a significantly increased risk of depression (adjusted hazard ratio (aHR) = 1.04, 95% CI: 0.79–1.36, P  = 0.804), and ART-treated men who remained childless did not have a significantly increased risk of developing depression compared to ART treated men who became fathers (aHR = 1.13, 95% CI: 0.87–1.48, P  = 0.355). LIMITATIONS, REASONS FOR CAUTIONS: Only severe cases of depression are recorded and included in this national register-based study given that only men with clinically diagnosed unipolar depression recorded in a psychiatric hospital (in-patient and out-patient) are included in the Danish PCRR. It is difficult to completely rule out an association between the exposures and depression as this outcome is so rare, and therefore the results are still statistically uncertain despite a large cohort. Furthermore, only men in ART treatment were included in this study, and caution should be taken in generalising findings to the total population of men in all areas of medically assisted reproduction or infertile men who have not sought treatment. WIDER IMPLICATIONS OT THE FINDINGS: This large national cohort study suggests that despite evidence showing that male factor infertility is a potential severe stressor for men, which can increase psychological distress and negative emotions, infertile men in ART treatment and men remaining childless after ART are not at a significantly increased risk of developing clinically diagnosed unipolar depression. STUDY FUNDING/COMPETING INTERESTS: C.S.S. was funded by unrestricted research grants received by Lone Schmidt from The Danish Health Insurance Foundation (J.nr. 2008B105) and Merck Sharp & Dohme (MSD). The sponsors had no influence on how data were retrieved and analysed or on the conclusions of the study. C.S.S. and L.S. have declared conflicts of interests; the remaining co-authors have no conflicts of interests to declare. TRIAL REGISTRATION NUMBER: Not applicable.